Numerical Evaluation of Pile Group Behavior Subject to Earthquake Loads (Journal of Engineering, 2024)
The seismic design of pile foundations mainly relies on analyzing the seismic response of layered, liquefiable locations. Two design scenarios are taken into consideration from the case histories; the first is how pile foundations react to the stresses and lateral displacements brought on by the lateral dispersion of liquefied soil. The second is how to piles reaction to seismic activity that occurs with the development of high pore water pressures. The PLAXIS 3D software is utilized in this research with a non-linear soil constitutive model (hypoplastic model) for both dry and saturated loose sandy soils under the impact of two earthquakes and the motion of different features to give a complete understanding of the dynamic piled foundation response. The findings from this study show that the site profile, pile diameter, pile length, and excitation of ground motion significantly affect the dynamic response of the layered liquefied site. So, in the saturated case, the increase in the piles length to (L/D = 55) in comparison to the original length (L/D = 35) decreased the peak acceleration at the raft foundation by about (24.4 and 41.9) % under the effect of Kobe and Upland earthquake motion, respectively, while in the dry case, the reduction in peak acceleration was about (22.8 and 40.9) % under the effect of Kobe and Upland earthquake motion, respectively.